Fuzzy State Observer Design for Engine Torque Control System of Spark Ignition Engine - Triwiyatno, Aris; Nuh, Mohammad; Santoso, Ari; Sutantra, I Nyoman (Transmisi, 2009)
The T-S (Takagi-Sugeno) model approach consists to construct nonlinear or complex dynamic systems that cannot be exactly modeled, by means of interpolating the behavior of several LTI (Linear Time Invariant) sub models. Since T-S observer based controller has been considered to develop some systematic design algorithms to guarantee the stability and specific performances for the T-S model based systems, this paper represent a new design of fuzzy state observer to estimate the states of engine torque control system of spark ignition engine. Keywords: T-S model, T-S observer, fuzzy state observer, engine torque, spark ignition engine.